Optimalisasi Pemasaran dan Penjualan Produk UMKM Melalui Pengembangan Sistem Informasi Berbasis User Centered Design - Misrawati Aprilyana Puspa; Sinta Suleman; Citra Yustitya Gobel; Zufrianto K. Dunggio; Alya Wahid (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
This study aimed to optimize the marketing and sales processes of MSME processed products through the development of an Android-based information system using the User Centered Design approach. The identified problems indicated that most MSME actors still conducted marketing and sales activities conventionally, resulting in limited promotional reach, less effective transaction management, and difficulties for consumers in accessing product information. This research was conducted using the User Centered Design method, which focused on user needs and experiences through the stages of interviews, observations, needs analysis, system design, implementation, and application testing. The results showed that the developed information system was able to assist MSME actors in managing product data, conducting digital promotions, and recording sales transactions more effectively and systematically. The Android-based application provided convenience for the community and business actors to access product information and carry out promotions anytime and anywhere through smartphones. The implementation results demonstrated a 75% increase in the marketing and sales of MSME processed products after the application was utilized. Therefore, the developed information system was able to support the digital transformation of MSMEs and improve marketing effectiveness as well as product competitiveness in a broader market.